Total Synthesis of Echinoside A, a Representative Triterpene Glycoside of Sea Cucumbers. Issue 26 (31st May 2017) - Chen, Xiaoping; Shao, Xiaofei; Li, Wei; Zhang, Xiaheng; Yu, Biao
Abstract: Echinoside A, a sulfonylated holostane tetrasaccharide with potent anticancer and antifungal activity, was synthesized in a longest linear sequence of 35 steps and 0.6 % overall yield. The synthetic approach is adaptable to the synthesis of congeners and analogues, as exemplified by the ready synthesis of ds‐echinoside A and echinoside B, and thus will facilitate in‐depth studies on the promising biological effects of echinoside A. Moreover, the present synthesis demonstrates the feasibility of synthetic access to the characteristic complex triterpene glycosides that occur ubiquitously in sea cucumbers. Abstract : Hand over your weapons, cucumbers ! Echinoside A (see structure), a sulfonylated holostane tetrasaccharide with potent anticancer and antifungal activity, was synthesized by an approach shown to be adaptable to the preparation of congeners and analogues. Importantly, the synthesis demonstrates the feasibility of synthetic access to the characteristic complex triterpene glycosides that occur ubiquitously as defense chemicals in sea cucumbers.